Factors of retention in the first year of high school students at the Universidad de La Serena - Avilés Pizarro, Ana María (2022)
The objective was to determine the factors that influence retention in the first year of secondary technical-professional education of students entering the Universidad de La Serena (2010 to 2015). The correlational study determines the retention of the socioeconomic and academic factor; it specifies the association between the variables. The study population was 1119 students, retention is 79.3%. Most of the students come from the Coquimbo region, the average age is 20 years, there are more men than women, and the predominant family income is from $74,970 to $193,104 (Chilean pesos). For the statistical analysis software SPSS version 22 is used, Chi-Square Test is applied to determining the relation between variables and Binary Logistics Regression searching the predictive model of retention and specify how the socioeconomic and academic factor influences it. The factors have different importance within the model, its importance depends on the value of the odds ratio (OR). Predict Retention is the University Records Rate (OR= 21,683) and Mathematics University Admission Test (OR = 8.489). The research determinate that lower Mathematics University Admission Test scored, higher Retention Probability.